DEVELOPMENT OF CONCEPTUAL CHANGE INSTRUMENTS TO MEASURE STUDENTS' UNDERSTANDING OF VIBRATIONS, WAVES, AND SOUNDS AT UNIVERSITIES - Lizelwati, Novia; Halim, Anis Diyana Bt; Mustapa , Izan Roshawaty binti (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2025)
The significant number of misconceptions students have about the concepts of vibration, waves, and sound poses a major challenge to learning physics in higher education. This study aims to develop a conceptual change instrument to measure student understanding of these topics using the ADDIE model (analysis, design, development, implementation, evaluation). The instrument is designed as a three-tier diagnostic test that includes multiple-choice (conceptual answers), open-ended reasoning, and the Confidence Rating Index (CRI). Content validity was tested using the Content Validity Index (CVI) with an S-CVI/ave result of 1.00, while reliability was tested using Cronbach's Alpha with a value of 0.756. The trial was conducted on first-year students of the Physics Education Study Program at Universitas Islam Negeri (UIN) Mahmud Yunus Batusangkar who were selected through purposive sampling. The results showed a big improvement in understanding concepts after using multi-representation inquiry-based learning, and the instrument was effective at identifying scientific understanding, misconceptions, and conceptual ignorance. These findings confirm that the multi-tiered approach with CRI is effective as a formative evaluation instrument in physics education.